Enhancement of the tidal disruption event rate in galaxies with a nuclear star cluster: from dwarfs to ellipticals. Issue 2 (7th July 2020) - Pfister, Hugo; Volonteri, Marta; Dai, Jane Lixin; Colpi, Monica
ABSTRACT: We compute the tidal disruption event (TDE) rate around local massive black holes (MBHs) with masses as low as 2.5× 10^4 M_, thus probing the dwarf regime for the first time. We select a sample of 37 galaxies for which we have the surface stellar density profile, a dynamical estimate of the mass of the MBH, and 6 of which, including our Milky Way, have a resolved nuclear star cluster (NSC). For the Milky Way, we find a total TDE rate of 10^-4 yr^-1 when taking the NSC in account, and 10^-7 yr^-1 otherwise. TDEs are mainly sourced from the NSC for light (3× 10^10 M_ ) galaxies, with a rate of few 10^-5 yr^-1, and an enhancement of up to two orders of magnitude compared to non-nucleated galaxies. We create a mock population of galaxies using different sets of scaling relations to explore trends with galaxy mass, taking into account the nucleated fraction of galaxies. Overall, we find a rate of few 10^-5 yr^-1 which drops when galaxies are more massive than 10^11 M_ and contain MBHs swallowing stars whole and resulting in no observable TDE.